Assessment of knowledge and usage of HIV post exposure prophylaxis among healthcare workers in a regional hospital in Ghana - Felicia Babanawo; Abdallah Ibrahim; Ozge Sensoy Bahar; Augustine Adomah-Afari; Ernest Maya (Journal of Global Health Reports)
# Background